Digital rights management and access to information : a developing country’s perspective - Nicholson, Denise Rosemary (2021)
Digital rights management systems (DRMs) together with technological protection measures (TPMs) have become a controversial topic of discussion around copyrighted works, particularly since the controversial Sony BMG case. This paper addresses some of the concerns around TPM-enabled digital rights management systems as they apply to and impact on developing countries. It highlights issues such as digital censorship, international support for digital rights management and the current legislation in South Africa relating to digital rights management. It also discusses types of digital rights management systems and how they affect access to information and knowledge, as well as their impact on the public domain and privacy. The paper provides some recommendations and challenges to librarians and educators in South Africa and for librarians in other developing countries, on how to address digital rights management issues in relation to their obligations and mandates to provide users and learners with unrestricted access to information.